The Effect of Game Modification on Relay Running on Student Excitement at SMA Negeri 21 Surabaya - Iswanto, Faris Wahyu; Priambodo, Anung (Jurnal Pendidikan Jasmani (JPJ), 2024)
In physical education, a pleasant atmosphere is needed. Because physical education is a subject that can help students get rid of boredom from learning subjects that are considered difficult. With a pleasant atmosphere in the learning material, students will feel comfortable and not feel forced when the teacher gives them movement assignments. An example is providing a game modification of one of the materials, which can be considered quite boring because it only focuses on physical activities and technical learning, namely athletic material. One of the numbers in athletics that can be used for game modification is the relay race, which can build a sense of cooperation between students. By providing game modifications to the relay race, students will feel more happy and comfortable when doing physical education learning on athletics material. Not only can the atmosphere make you happy, but it can also increase students' interest in learning physical education because they feel comfortable. To determine the level of student excitement, the tool used is an instrument in the form of a joy questionnaire. With the help of SPSS 26 to process the data after the research is done. The results of the research conducted showed that students who received therapy were more enthusiastic than those who did not. The percentage of students who received therapy was 46.19%, while the number of students who did not receive therapy was 9.5%.